Possibility of development of civil defense in Republic of Belarus by creation of uniform state system of civil protection - Bordak Сергей; Subbotin Михаил; Tikhonov Максим (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2015)
Current foreign state systems of population protection from military attacks and emergency situations in peacetime have been analyzed and characterized. The possibility of creation and structural scheme of state system of civil defence is considered which provides the protection of population from military attack, and natural as well as human-made disasters.